Respons Parameter Eritrogram Sapi Perah Peranakan Friesian Holstein Laktasi terhadap Suplementasi Daun Lamtoro (Leucaena leucocephala): Response of Lactating Friesian Holstein Crossbred Dairy Cows Erythrogram Parameters to Lamtoro Leaf (Leucaena leucocephala) Supplementation (Jurnal Ilmu Nutrisi dan Teknologi Pakan, 2026)
Optimizing the physiological status of lactating dairy cows is greatly influenced by feed quality, particularly the availability of adequate protein and minerals to support systemic functions. This study was conducted to evaluate the erythrocyte response of lactating Peranakan Friesian Holstein (PFH) dairy cows supplemented with lamtoro leaves (Leucaena leucocephala). Twelve lactating PFH dairy cows, aged 3–4 years, in the 4th to 8th month of lactation, and with an average body weight of 450 kg, were placed in a Randomized Block Design (RBD) consisting of two treatments and six blocks. The diet consisted of a 40:60 ratio of forage to concentrate, with the concentrate comprising rice bran, coconut meal, coffee husks, wheat flour, vitamins, minerals, and soybean meal. Lamtoro leaf supplementation was 10% for P0 and 20% for P1 based on the dry matter of the forage. Blood samples were collected via the jugular vein for analysis of hemoglobin (Hb), red blood cell count (RBC), hematocrit (Hct), and indices including Mean Corpuscular Volume (MCV), Mean Corpuscular Hemoglobin (MCH), and Mean Corpuscular Hemoglobin Concentration (MCHC). Data were analyzed using ANOVA followed by Duncan’s test. The results showed that the addition of lamtoro had a significant effect (p